Presence of the Wheat Curl Mite, Aceria tosichella Keifer (Prostigmata: Eriophyidae), in Uruguay - Castiglioni, Enrique; Navia, Denise (Agrociencia Uruguay, 2010)
The Wheat Curl Mite (WCM), Aceria tosichella (Keifer), a vector of important virus that affect wheat and corn, was recently detected in South America, in Argentina. This found alerted to the risk of dissemination of the pest to neighbor countries in the continent. Aiming to determine the status of the WCM in Uruguay, a survey of eriophyid mites associated with wheat, barley, corn and other common grasses was conducted in the main wheat production areas of this country, in November 2007. WCM specimens were collected from wheat, Triticum aestivum L., in Ombúes de Lavalle, Tarariras and San Juan, Department of Colonia and in San Javier, Department of Río Negro; and also from ryegrass, Lolium multiflorum Lam (Rosario and San Juan, Colonia; Cardona, Soriano) and brome, Bromus unioloides (Willd.) Kunth (Rosario, Colonia). This is the first report of A. tosichella in Uruguay and also the first time the mite is found, in field surveys, on other hosts different from wheat in South America.